Can Clinical Skill Laboratories (CSLs) be Online? - Sadia Choudhury Shimmi; M. Tanveer Hossain Parash; Fairrul Masnah @ Kadir (Penerbit UMS, 2022)
Clinical skill laboratories (CSLs) are integrated community, objective, and outcome-based learning processes that integrate basic knowledge with clinical skills. CSLs are hospital or medical school-based teaching which includes self-directed, student-centered and problem-based learning. CSLs can be taught in the procedural room, out-patient department, primary healthcare center, casualty department, and simulation settings (Al-Elq, 2007). Experienced clinician, a small group of self-motivated students, cooperative patients, adequate and reliable instruments, enough time to practice, and a comfortable room with adequate ventilation are factors for effective CSLs (Ramani & Leinster, 2008). The teaching activities and learning can be face-to-face or blended learning, e-learning and online learning. Nowadays, blended and online learning is gaining more popularity. Blended learning combines face-to-face and online learning that supports creative, critical thinking skills (Garrison & Kanuka, 2004). Synchronous and asynchronous learning is the part of online learning where teachers use video and audio technologies (Gormley et al., 2009).